Construction of multi-functional optical sensing materials based on deazapurine-typed carbon dots. (February 2021) - Su, Linlin; Shi, Binbin; Hang, Yixiao; Xian, Chensheng; Huang, Jin
Abstract: Developing multi-functional materials is crucial to manufacture integrated devices and advanced instruments. However, the development of multi-functional properties is limited because most of the materials can only perform single-phase processing or detection. In this current study blue-emitting, amphiphilic purine-doped and amphiphilic carbon dots (CDs) have been synthesized for the construction of multi-functional materials. These multi-functional CDs (MF-CDs) can form stable dispersions of monodisperse nanoparticles or nanoaggregates in organic/aqueous phase, which endow them with the capability to be either processed or used as detectors/sensors in a variety of solvents. The MF-CDs not only can detect pH, metal cations and the polarity of organic solvents via the change of fluorescent signals in the solution state, but also can be applied in the fields of temperature response and laser-stimulus response in a composite film. As a consequence of the architecture of the MF-CDs composite systems multi-functional characteristics can be realized successfully, which provides a new perspective to develop integrated materials at the nanoscale level. Graphical abstract: Image 1 Highlights: Amphiphilic nitrogen doped MF-CDs with blue emission was synthesized via solvent-thermal method. MF-CDs exhibited high sensitivity and selectivity to pH, the polarity of solvent and metal ions in solution. Two kinds of MF-CDs doped composites can be applied to rapid laser-response and fluorescence temperature sensing.